ANALYSIS OF THE EFFECT OF FINANCIAL RATIO ON SHARE PRICE AT PT UNILEVER INDONESIA TBK PERIOD 2010-2021 - Sulaiman, Asep; Herlina, Listri (Journal of Business and Management Inaba, 2023)
PT Unilever Indonesia Tbk experienced problems with declining stock prices. Company performance is a factor that can cause a decline in stock prices. Whether a company's performance is good or not can be seen from financial ratios such as CR, DER, NPM, EPS and PER, where investors tend to invest funds in companies with good financial ratios. The research objective was to determine the effect of CR, DER, NPM, EPS and PER on stock prices at PT Unilever Indonesia Tbk for the 2010-2021 period. Quantitative research method with a descriptive verification approach. Secondary data sources in the form of annual financial report data and purposive sampling technique. data analysis techniques with descriptive analysis, regression, correlation, hypothesis testing both partially and simultaneously and analysis of the coefficient of determination, with the help of the SPSS v24 program. The results of the study show that in testing the hypothesis the results are: (1) CR has no significant effect on stock prices. (2) DER has a significant effect on stock prices. (3) NPM has a significant effect on stock prices. (4) EPS has a significant effect on stock prices. (5) PER has a significant effect on stock prices. (6) CR, DER, NPM, EPS and PER provide a simultaneous effect (together) on the stock price.